2012
DOI: 10.1128/aem.01739-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Identification of a High-Affinity Ni Transporter and the Transcriptional Response to Ni Deprivation in Synechococcus sp. Strain WH8102

Abstract: dOne biological need for Ni in marine cyanobacteria stems from the utilization of the Ni metalloenzyme urease for the assimilation of urea as a nitrogen source. In many of the same cyanobacteria, including Synechococcus sp. strain WH8102, an additional and obligate nutrient requirement for Ni results from usage of a Ni superoxide dismutase (Ni-SOD), which is encoded by sodN. To better understand the effects of Ni deprivation on WH8102, parallel microarray-based analysis of gene expression and gene knockout exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 66 publications
(98 reference statements)
3
28
0
Order By: Relevance
“…Comparing the results of this study to previous microarray experiments on the response of marine Synechococcus to nutrient limitation [phosphate starvation (Tetu et al, 2009), (Ostrowski et al, 2010)] heavy metal stress [copper toxicity (Stuart et al, 2009)] and nickel starvation (Dupont et al, 2012), it appears that the transcriptional response to different “types” of stress tend to be quite specific and can differ substantially between strains. In each study the set of genes showing the highest transcriptional increase differed.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Comparing the results of this study to previous microarray experiments on the response of marine Synechococcus to nutrient limitation [phosphate starvation (Tetu et al, 2009), (Ostrowski et al, 2010)] heavy metal stress [copper toxicity (Stuart et al, 2009)] and nickel starvation (Dupont et al, 2012), it appears that the transcriptional response to different “types” of stress tend to be quite specific and can differ substantially between strains. In each study the set of genes showing the highest transcriptional increase differed.…”
Section: Resultssupporting
confidence: 55%
“…The large number of datasets concerning transcriptional responses of WH8102 to a range of stress conditions [copper toxicity (Stuart et al, 2009), phosphate starvation (Tetu et al, 2009) and nickel starvation (Dupont et al, 2012)] enabled us to conduct cluster analyses which revealed a cluster of stress related genes upregulated in most treatments (Figure 2). This set of upregulated genes encodes functions such as Clp endopeptidase, heat shock proteins, chaperones and cell division proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent molecular innovations are employed by organisms in the modern environment to reduce Fe requirements-but always with a tradeoff. These tradeoffs include; the replacement of a Fe-containing superoxide dismutase with a Nicontaining version (Dupont et al, 2012), exchanging an Fe protein with a Cu protein in the electron transport chains in photosynthesis (Peers and Price, 2006) and ammonia oxidation (Santoro et al, 2015), and using B 12 instead of Fe for ribonucleotide reductase.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In another study, the genome-wide metabolic network of S. elongatus PCC 7942 was reconstructed by metabolic flux simulation models, and the applicability of the model was demonstrated by simulating the autotrophic growth conditions of this strain (Triana et al, 2014). Comparatively, parallel microarray-based analysis of gene expression and gene knockout experiments were conducted for Synechococcus sp WH 8102, and the results showed that the sodT::sodB exconjugants were unable to grow at low Ni concentrations while the sodN::sodB exconjugants displayed higher growth rates at low Ni concentrations than did the wild type (Dupont et al, 2012).The genome sizes of the common Synechococcus strains are less than 3Mb and the numbers of genes are less than 3000. However, the genome of the newly sequenced strain S.PCC7336 is over 5Mb, and is therefore likely to carry unique structures and functional genes.…”
Section: Introductionmentioning
confidence: 99%